ABUNDANCE AND DISTRIBUTION PATTERN GASTROPODS IN THE MANGROVE ECOSYSTEM OF TANJUNG BALAI DISTRICT ASAHAN REGENCY, NORTH SUMATRA PROVINCE - Windy Anjeli Hutahaean; Thamrin Thamrin; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis study aims to determine the type, abundance and distribution patterns of gastropods in the mangrove ecosystem of Tanjung Balai District. This research was conducted in March 2019 in the mangrove ecosystem of Tanjung Balai District, Asahan Regency, North Sumatra Province. The method used in this study is survey method by determining the location of the station using purposive sampling method. Gastropod sampling in the mangrove area using line transects and plots (Line Transect Plots). The transect is stretched along 50 meters, starting from the initial boundary of the mangrove landed towards the sea. At each station there are 3 transects and each transect is placed 3 plots measuring 1x1 m².The results obtained by 6 families of gastropod species from 4 families. The highest species abundance at all stations is Nassarius sp. Abundance of gastropods is significantly different. Grouped Distribution patterns. The average temperature in the range of 27,7-29ºC, salinity is in the range of 28,3-29,7 ppt, the acidity (pH) is in the range of 6-7, and organic materr ranges of17,79% - 21, 09%. Sandy mud substrate type.Keywords: Gastropods, Abundance, Distribution patterns, Mangrove ecosystem, TanjungBalai